Polyaniline-based field effect transistor for DNA/RNA biomarker sensing: Comparison to electrochemical impedance and inorganic layer - Pedroza Dias Mello, Hugo Jose Nogueira; Bachour Junior, Bassam; Mulato, Marcelo (Elsevier B.V., 2021)
One relevant aspect of the research in materials science focus on studying materials properties for applications in the field of sensing and biosensing devices aiming to obtain portable, stable, sensitive, and low-cost detection systems for a broad range of diseases, traumas, and infections. We report a polyaniline (PANI)-based extended-gate field effect transistor DNA/RNA (DNA-EGFET) biosensor. The biosensor is based on a functionalized Au reference electrode with thiolated bio-receptor single-strand DNA (ssDNA) corresponding to the mu DNA-224, an overexpressed DNA biomarker sample for rectal colon cancer, and the transduction system is based on an electrodeposited PANI thin film as sensing stage. Variations on net surface charge of the hybridized single strand DNA led to changes of the output voltage from the FET system, which could be correlated to the concentration of the detected complementary DNA. Comparison between the potentiometric EGFET biosensor and the electrochemical impedance spectroscopy (EIS) biosensor used for DNA/RNA measurements and the use of organic and inorganic (metal oxide) semiconducting sensing materials were performed. This DNA-EGFET biosensor offered fast response, sensitivity of 3.3 +/- 0.3 mV/log[tDNA], linearity of 96 % in a detection range from 1 pmol/L to 1 mu mol/L and LoD of 9.77 pmol/L in buffer solution. The application and comparison of the PANI based DNA-EGFET for measurements of DNA biomarkers was demonstrated as a proof-of-concept of the advantages and easy fabrication of the device. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Field-effect transistor; Impedimetric; Semiconducting polymer; Biosensor; DNA